PENERAPAN STRATEGI MULTIPLE INTELLIGENCES UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 001 ROKAN IV KOTO - Repitadara Repitadara; Mahmud Alpusari; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was carried out because of the low yield learning IPA of fourth grade students of SDN 001 Rokan IV Koto, KKM assigned in school, that is 75.From the 27 students, who reached the KKM was just 10 students (37,04%), whereas students who have not yet reached the KKM was 17 students (62.96%) with an average rating of class 64.11. The purpose of this research is to improve learning achievement of IPA studies of fourth grade students of SDN 001Rokan IV Koto with the implementation of the strategy of multiple intelligences. The research results obtained average value score increased 64.11 basic cycle I of 13.22% to 72.59. In cycle II, the average value of the students also experienced an increase of 27.37% to 81.66. On a base score of classical succes learning of student was 37,04% IPA (not succes). After multiple intelligences strategies applied in cycle I studied classical succes of students increased to be 59.26% (not succes) and on cycle II classical succes learning of students increased to 85.19% (succes). The activity of the teacher in the first meeting of the cycle I got was 64.28%. The second meeting was increased to 78.57%, and at the third meeting of the cycle I increased to 82.14%. At the first meeting of the cycle II teacher activity increased to 89.28%. At the second meeting increased to 92.85% by very good category. The activity of the students at the first meeting of the cycle I got was 60.71%. The second meeting was increased to 75.00% by enough category, and at the third meeting of the cycle I increased to 78.57%. On first meeting in cycle II student activity increased to 82.14%. At the second meeting increased to 85.71%. From this research it can be concluded that by implementing a strategy of multiple intelligences can improve IPA learning achievement of fourth Grade students of SDN 001Rokan IV Koto.Keywords: Strategy of multiple intelligences, Achievement of IPA study